Design evaluation of development policies in Brazilian capitals:: endogeneity and governance - Lima, Luciana Leite; D’Ascenzi, Luciano (Revista Aval, 2022)
This article assesses the design of public policies for local development formulated by the municipal governments of 14 selected state capitals. An analytical approach was outlined based on two sets of categories drawn from the perspective of endogenous development: endogeneity (in the dimensions: equity, sustainability and participation) and governance mechanisms (in the dimensions: participation, consensuality and mixed management). Documentary research was carried out; collection was carried out online between August 2017 and May 2018; in all, 407 documents were analyzed. It was found that the design characteristics of these policies indicated inconsistencies with contemporary notions of development, as they overvalued the dimension of economic growth; and, not by chance, a fragile element was that of sustainability. A promising point was the equity dimension, as well as the heterogeneity of societal and state actors.